Effectiveness of color coded diabetic control monitoring charts among elderly diabetics attending outreach primary care geriatric clinics in rural Karnataka: An open label randomized control trial - Farah N Fathima; Neethu George; Meera George; Savan Sara Mathew; M Rajitha; Twinkle Agrawal; Arvind Kasturi (Wolters Kluwer Medknow Publications, 2019)
Introduction: Type 2 diabetes mellitus problem is progressively rising every day. The adherence to the treatment approaches and health-seeking make major difference in case of diabetics particularly elderly. Visual tools improve the involvement of patients in their care, especially among populations with low health literacy. Objective: To evaluate the effectiveness of color-coded diabetic control monitoring charts on glycemic control among elderly diabetics. Methodology: 144 elderly diabetic patients attending rural primary care geriatric clinics were randomized into two groups. Those randomized to the intervention group received the color-coded diabetic monitoring chart and a health education package in addition to the usual consultation services. Baseline and 1-year follow-up glycated hemoglobin (HbA1C) values were used to assess the effectiveness of the intervention. Results: The results of multivariate linear regression analysis showed that there was an average reduction of 0.265% in HbA1C value in the intervention group when compared to the nonintervention group when adjusted for baseline HbA1C and number of visits during the intervention period (β coefficient = 0.265,P < 0.05). Conclusion: Color-coded diabetes charts are effective in achieving glycemic control among elderly diabetics, and steps should be made to inculcate visually appealing management approaches in case of elderly diabetic patients.